Lack of the Association of the PTPN22 C1858T Gene Polymorphism With Susceptibility to Familial Mediterranean Fever - Orhan KÜÇÜKŞAHİN and Zeynep ŞEKER and Ali ŞAHİN and Gülay KINIKLI and Timur TUNCALI and Murat TURGAY and Alexis K OKOH and Emre KÜLAHÇIOĞLU and Şükran ERTEN and Aşkın ATEŞ (Archives of Rheumatology, 2016)
Objectives: This study aims to investigate whether the protein tyrosine phosphatase non-receptor type 22 (PTPN22) C1858T gene polymorphism plays a role in the pathogenesis of familial Mediterranean fever (FMF) through T-lymphocyte activation. Patients and methods: We conducted a case-control study with 180 FMF patients (68 males, 112 females; mean age 38.2±1.6 years; range 16 to 81 years) and 184 healthy controls (86 males, 98 females; mean age 32.9±9.2 years; range 18 to 58 years). The PTPN22 C1858T polymorphism (rs2476601) was genotyped by polymerase chain reaction restriction fragment length polymorphism. In patients with FMF, clinical features, disease severity score, the frequencies of amyloidosis, positive family history, and Mediterranean fever gene mutations were determined. Results: The frequencies of heterozygous genotype (CT) were 4.5% in FMF patients and 2.8% in healthy controls, respectively. The frequencies of polymorphic homozygous genotypes (TT) were 0.5% in both FMF patients and healthy controls. There were no statistically significant differences in the frequencies of CT and TT genotypes between FMF patients and healthy controls (odds ratio: 1.65, 95% confidence interval: 0.53-5.14, p>0.05 for CT genotype). The frequencies of clinical features, sex, amyloidosis, positive family history, Mediterranean fever gene mutations, and disease severity score were not significantly different between the patients. Conclusion: The distribution of PTPN22 C1858T polymorphism did not reveal any association with FMF in a Turkish population.